(untitled) (Nexo Revista Científica, 2022)
The authors conducted this study to assess the influence of the strength properties of packaging materials for baked confectionery products on the tensile strength, fracture strength, and elongation level. The purpose of this study was to evaluate the mechanical properties (impact strength, fracture strength, and distance to fracture). The paper presents a brief overview of modern methods of functional and operational properties control for polymer packaging materials used for food products and describes their features. The objects of the study were samples of packaging for gingerbread purchased from trade organizations. It has been shown that quality control of polymer packaging materials for food is key in determining the possibility of their intended use. The test results allow evaluating the possibilities and limitations, optimizing the technological process, and obtaining high-quality packaging. In conclusion, the authors give recommendations to gingerbread manufacturers to increase the competitiveness of the product and meet consumer demand.